Implementación de una gestión por procesos en la prestación del servicio de capacitación de la Fundación Educativa CAMAE - Caballero Pérez, Selene Raquel (2014)
The implementation of process management is, undoubtedly, a great tool for the development of the activities of an organization that is always looking for continuous customer satisfaction and improvement of its services. Process management allows knowing the procedures, and therefore, the proper execution of tasks for a particular plan. It also creates liability, and it is a great way for recording employee performance. At the same time, regular monitoring of results provides an opportunity to prevent, correct, or adopt new measures to ensure continuous improvement. CAMAE Educational Foundation (FCAMAE) has the ability to establish an appropriate administrative structure, with a distribution of responsibilities that are aligned with the functions of each position. Moreover, CAMAE Educational Foundation has predefined the qualifications and skills that employees will need to have or acquire for the different positions within a company. Process management provides an overview for running a business and simplifies all operations while establishing a duties and procedures guide that provides all the necessary information to define, visualize, measure, control, report and improve processes to meet a company's goals.